Effects of Iranian Healthcare Transformation Plan on Discharge against Medical Advice - Hajiesmaeilpoor, Ayshe; Mohammadnejad, Esmaeil; Shameli, Alireza; Sadat Izadi- Avanji, Fatemeh (International Journal of Psychosocial Rehabilitation, 2020)
Background: The healthcare transformation plan (HCTP) is expected to improve the regulations and quality of the provided services in hospitals. The aim of this study was to evaluate the effects of the Iranian healthcare transformation plan on discharge against medical advice (DAMA) of Mazandaran University of Medical Sciences. Method: This descriptive-retrospective study was performed on 2630 patients discharged during the two half-yearly time intervals before (2013-2014) and after (2015-2016), respectively. Data collection was by the standard form of DAMA issued by the Ministry of Health and Medical Education. Data analyses were performed using descriptive statistics and inferential statistics. SPSS-16 software was used in this study, and P values less than 0.05 were considered significant. Results: The level of DAMA before and after the introduction of the Healthcare Reform was 4.5 and 4.11 percent, respectively, which did not differ significantly (p = 0.889). In addition, there was no significant difference in the discharge level by age groups, hospital departments (p = 1), gender (p = 0.57), or holidays (p = 0.73). Conclusion: Our study did not find any evidence for the impact of the HCTP on the frequency of the DAMA and the factors associated with it. However, the overall results implied the necessity of more comprehensive and integrated planning regarding the supply of the required facilities, equipment, and human resources, as well as the enlargement of the physical space of treatment centers within the framework of this large-scale, nationwide program.